Cinema Reservation Through Mobile Application - Alnasar, Mohammad Rustom (2010)
Usability of mobile application is rapidly increasing, in the contemporary world. Moreover, regarding to the market and competition inside it; the company and most of businesses are using the technology to get profits and more customers in order to taking the cinema as one of the important things now and it does face great demands from the people. when we are looking for the booking processing, these processes need time and efforts from the customers. Most cinemas in the world have techniques to do reservation in the cinema via the web sites. Therefore, the aim of the this study is to develop mobile applications for movies cinemas' reservations because there are 90.3% of Malaysian people have mobile phone (commission, 2007), the study develops an application and a prototype to use mobile device to facilitate the reservation process.